Hot Water Epilepsy Successfully Treated With Daily Clobazam. Issue 10 (October 2017) - Ekici, Arzu; Ozdemir, Ozlem; Yimenicioglu, Sevgi; Oren, Ayse; Sen, Ismail
Abstract : Abstract: Hot water epilepsy (HWE) is a rare form of reflex epilepsy precipitated by a bath or shower in hot water. Although the condition is benign and a decreased bath temperature will help, antiepileptic drugs may be needed in some cases. Prophylactic clobazam is currently the first choice treatment option. Here we report the case of a 10-year-old boy with HWE successfully treated with daily doses of clobazam. Daily clobazam was preferred over prophylactic clobazam because of the patient's frequent bathing and parental concern. Daily clobazam is a novel treatment option for HWE and seems to be a good choice where antiepileptic drugs are necessary. Abstract : Supplemental digital content is available in the text.